Multichannel distribution strategy of Airbnb hosts - Sauveur Giannoni; Daniel Brunstein; Florian Guéniot; Johan Jouve (Annals of Tourism Research Empirical Insights, 2021)
The literature on the peer-to-peer hospitality market largely assumes that Airbnb hosts are loyal to the platform. However, similar to hoteliers, Airbnb hosts have access to various platforms to diversify their distribution channels. In cases where hosts significantly diversify their distribution channels, they should be considered rather as professional competitors mimicking hoteliers. Proposing an original image-recognition approach to obtain a proxy of the number of platforms used by Airbnb hosts, this paper assesses the probability that a home-sharer practices multichannel distribution. Drawing on a sample of more than 3900 hosts from the region of Corsica in France, we show that a multichannel distribution strategy is commonly adopted. Furthermore, a significant fraction of small hosts uses three or more channels.
Keywords: 330; Multichanne; Home-sharing; Airbnb; Zero-inflated models; Endogeneity